Influence of variations in the pressure distribution on the friction of the finger pad - Derler, S.; Süess, J.; Rao, A.; Rotaru, G.-M. (Tribology international, 2013)
We investigated the influence of the contact pressure distribution on the friction of the index finger pad. The skin contact pressure distributions were characterised by round profiles for low forces. At higher loads, the pressure distributions of the finger pad became asymmetric and conical. Additional experiments with the knuckle revealed pressure distributions with sharp peaks. The friction coefficients of the finger pad and the knuckle indicated a common behaviour in accordance with the adhesion friction model. Varying pressure distributions were found to influence the friction coefficients of skin, contributing to the variation of measurement results at comparable normal loads. ► Contact pressure distribution of the finger pad during friction varies with load. ► At small forces, finger pads show pressure distributions close to the Hertz model. ► At higher loads, pressure distributions of the finger pad are asymmetric and conical. ► Pressure distribution influences the friction coefficient of the finger pad.